Pemetaan Zona Potensial Penangkapan Ikan (ZPPI) Di Perairan Selat Bali Menggunakan Citra Satelit Aqua MODIS - Ni Kadek Ayu Dwi Lestari; I Dewa Nyoman Nurweda Putra; Ni Luh Putu Ria Puspitha (Department of Marine Sciences, Faculty of Marine and Fisheries, Universitas Udayana, 2023)
The abundance and distribution of fish are influenced by environmental productivity, such as chlorophyll-a distribution and variations in sea surface temperature (SST). The lack of technology fishermen use in the waters of the Bali Strait has resulted in the high potential of fish resources not being optimally utilized. This study aimed to determine potential fishing zones by utilizing Aqua MODIS satellite data which can detect SST and chlorophyll-a. The image data observed was from October to December 2018 to 2020. The method used is the Single Image Edge Detection Algorithm, where this algorithm is used to determine potential fishing areas designed to detect fronts in SST images. The results showed that in December 2018, 7 potential fishing points were produced, marked with a chlorophyll-a value of 0.25 mg/m3 and an SST of 29.25°C. In December 2020, 82 potential fishing points were produced, with a chlorophyll-a value of 0.31 mg/m3 and an SPL of 29.79°C. Validation was carried out by analyzing the result of image processing with fish catch data obtained from Pengambengan PPN, Muncar PPP, and Kedonganan TPI. SST, with a value of 27°C, is the ideal temperature for fish where when the temperature increases, the number of potential fish catch points decreases and vice versa. The distribution of chlorophyll-a content with a value of > 0.2 mg/m3 affects the number of potential fishing points, where the higher the chlorophyll-a content, the more fishing ground points and vice versa.